Searching for Values in the Empathetic Discourses of Business and Promotion - Kristina, Diah (Proceedings of English Linguistics and Literature, 2020)
Discourse provides insight on the function and nature of cognitive-emotional phenomena. Empathetic notions of a community can be traced from their discourses and how the community members use them, especially in the context of business and promotion. This paper explores how values are reflected in the English and Javanese empathetic business and promotional discourses especially the business and promotional idioms, expressions, taglines, and descriptions. 31 out of 50 online English empathetic business idioms and 21 out of more than 300 printed Javanese proverbs and sayings were analyzed using the perspectives of ESP with a thick description on the context of both cultures. Additionally, a reflective analytical lens was also included considering that the author is a Javanese herself who is using and practicing the Javanese language and culture on daily basis. Findings of the study suggest a strong ground of how cultural beliefs and values transmitted from the ancestors for-grounding the practice of business interactions with some innovations following changing of time and expectations.